2000
DOI: 10.21608/jpp.2000.260085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mean Performances, Genetic Parameters and Nutritive Values for Some Selected Strains of Forage Sorghum

Abstract: The shortage of green fodder for farm animal during summer has been increased in Egypt. Therefore, great efforts must be directed towards the improvement of summer forage crops. Sorghum could be provided as a solvent to this problem, since it is considered the most important forage crop during summer. This investigation is a contribution to improvement the sorghum fodder yield by selection.Selected 17 strains from F2 segregation generation of the superior hybrid between forage sorghum variety (Quna) and dwarf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similar results were obtained for plant height and stem diameter. Haggag [1] and Kumar Srivas and sing [2] in a similar study found that dry forage yield to be significantly and positively associated with fodder yield , plant height and stem diameter Moreover, Carpici and Celik [3] concluded that the relationship between dry forage yield and each of the yield components except leaf/stem ratio were positive and significant .Gheasemi et al [4] compared fifteen genotypes of fodder summer and found significant differences among the genotypes in fodder and dry yield . Maarouf and Moataz [5] and Gheasemi et al [6] evaluated some newly developed sweet sorghum genotypes for some forage attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained for plant height and stem diameter. Haggag [1] and Kumar Srivas and sing [2] in a similar study found that dry forage yield to be significantly and positively associated with fodder yield , plant height and stem diameter Moreover, Carpici and Celik [3] concluded that the relationship between dry forage yield and each of the yield components except leaf/stem ratio were positive and significant .Gheasemi et al [4] compared fifteen genotypes of fodder summer and found significant differences among the genotypes in fodder and dry yield . Maarouf and Moataz [5] and Gheasemi et al [6] evaluated some newly developed sweet sorghum genotypes for some forage attributes.…”
Section: Introductionmentioning
confidence: 99%